2019
DOI: 10.1002/hed.25619
|View full text |Cite
|
Sign up to set email alerts
|

Adjuvant radiation for positive margins in adult head and neck sarcomas is associated with improved survival: Analysis of the National Cancer Database

Abstract: Background Adult head and neck (H&N) sarcomas are a rare malignancy with limited data delineating the role of postoperative radiotherapy (PORT), particularly for a positive surgical margin. There are no randomized trials supporting the use of PORT, therefore treatment trends vary between institutions. A positive margin predicts recurrence and poor survival outcomes. This study uses the National Cancer Database (NCDB) to investigate whether PORT improves overall survival (OS) in adult H&N sarcomas with a positi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…At the latest audit in 2018, the overall data-consisting rate was 99.5%. For each involved patient, the following clinicopathological factors were retrospectively retrieved from the database: age, RT dose, pathologic stage, clinical stage, surgical margin, and postoperative adjuvant chemotherapy ( 17 19 ). All data were independently validated by a radiation physician and analyzed by a biostatistician according to methods described in the statistical section, as previously reported ( 12 ).…”
Section: Methodsmentioning
confidence: 99%
“…At the latest audit in 2018, the overall data-consisting rate was 99.5%. For each involved patient, the following clinicopathological factors were retrospectively retrieved from the database: age, RT dose, pathologic stage, clinical stage, surgical margin, and postoperative adjuvant chemotherapy ( 17 19 ). All data were independently validated by a radiation physician and analyzed by a biostatistician according to methods described in the statistical section, as previously reported ( 12 ).…”
Section: Methodsmentioning
confidence: 99%
“…Recently, several large population-based analyses were performed to overcome the limitations of small patient numbers and to clarify the value of additional RT (although limited by the inclusion of varying proportions of pediatric sarcomas, bone sarcomas or sarcoma-like histologies). Cannon et al [53] analyzed 1142 patients from the NCDB with margin-positive resections and found a significant benefit regarding 5-year-OS for the addition of radiation (57% vs. 48%). Subgroup analyses revealed that the benefit was found after microscopic and macroscopic incomplete resections with a similar magnitude (R1: 57% vs. 49%, R2: 57% vs. 41%) and was confirmed as an independent prognostic factor after controlling for other covariates which influenced OS according to multivariate analysis.…”
Section: Perioperative Rt In Head and Neck Sarcomasmentioning
confidence: 99%
“…24 Similarly, single institutional reports and studies using large datasets from 2 different cancer registries (Surveillance, Epidemiology, and End Results database and NCDB) have shown significant survival benefits of adjuvant RT for patients with head and neck sarcomas and extremity STSs, particularly in cases with high-grade tumors. 13,14,[25][26][27][28] Furthermore, a recent meta-analysis also concluded that RT is associated with lower long-term mortality in patients with surgically resected STSs when the results of high-quality studies (reporting adjusted HRs) are pooled. 29 For thoracic STSs, however, only a limited number of studies have reported single institution-based experiences regarding survival outcomes after adjuvant RT.…”
Section: Commentmentioning
confidence: 99%